The Capacity of Runway of Ngurah Rai International Airport Bali Based on The Doratask Method - Majid, Suharto Abdul; Larasati, Emilia Rahajeng; Rizaldy, Wynd; Setiawan, Edhie Budi; Pahala, Yosi; Agusinta, Lira; Ricardianto, Prasadja; Hernawan, Mochamad Arif (The journal of contemporary issues in business and government, 2021)
This research aims to know the runway capacity at Ngurah Rai International Airport Denpasar Bali using the Doratask Method. Doratask Method is the method of calculating the capacity of runway adopted from the ICAO project 2009, which is also used to analyze the size of a runway in several ICAO country members in the South America Region (SAM Region). Observation, documentation, interview, and literature study are carried out to obtain the data of runway capacity at Ngurah Rai Airport Bali. The sample in this study is the data of aircraft movements for about 12 hours of flight during peak hours. Direct observation is done for seven full days on runway 09 and runway 27. The research finds the value of runway capacity at Ngurah Rai Airport Bali as many as 18 aircraft movements. The condition of Ngurah Rai Airport when the survey is done is that it can accommodate around 15 changes. It means the runway capacity at Ngurah Rai Airport Bali has been overcapacity. The use of Doratask Method to calculate runway capacity is considered most suitable to be implemented at Ngurah Rai Airport Bali because the value is close to the real condition in the field in line with the philosophy of runway capacity, that is the capability of runway to accommodate the aircraft movements for take-off and landing with no delay